GAMBARAN PERILAKU AGRESIF ANAK USIA DINI DI TAMAN KANAK-KANAK ALAM MINANGKABAU - Nadila, Putri; Izzati, Izzati (Jurnal Warna, 2019)
This reseacrh aims to describe the aggressive behavior of early childhood in the Alam Minangkabau Kindergarden. The research method used is descriptive research using a qualiative approach. Data collection techniques in the form of observation, interviews and documentation. The results of the study started that childrend in the Alam Minangkabau Kindergarden had aggressive behavior, which was seen based on aggressive forms of behavior namely physical aggressive behavior and verbal aggressive behavior.